Kinematic comparison of the roundhouse kick between taekwondo, karate, and muaythai - Diniz, R.; Del Vecchio, F. B.; Schaun, G. Z.; Oliveira, H. B.; Portella, E. G.; da Silva, E. S.; Formalioni, A.; Campelo, P. C. C.; Peyré-Tartaruga, L. A.; Pinto, S. S. (The Journal of Strength and Conditioning Research, 2021)
The roundhouse kick (RHK) is frequently executed in taekwondo, karate, and muaythai because of its high technical effectiveness during combat. The purpose of this study was to compare kinematic characteristics during RHK performance between taekwondo, karate, and muaythai athletes. Forty-seven male athletes (25.5 ± 4.7 years, 1.75 ± 0.1 m, and 75.8 ± 11.5 kg) volunteered to participate (taekwondo: 17; karate: 15; and muaythai: 15). Self-selected distance from target, mean and peak fifth metatarsus linear velocity (LV5mean; LV5peak), mean and peak hip (HAVmean; HAVpeak) and knee (KAVmean; KAVpeak) angular velocities, as well as target linear acceleration (TLA) were analyzed with a 3D video motion analysis system. Comparisons between modalities were performed with 1-way analysis of variances and Bonferroni's post hoc test (a = 0.05). Self-selected distance was lower in muaythai compared with taekwondo and karate (p < 0.001). Also, karate had greater LV5mean compared with muaythai (p = 0.001), and muaythai showed higher HAVmean than karate (p = 0.011). In addition, HAVpeak was greater in muaythai than in taekwondo and karate (p < 0.001). No differences were found for KAVmean, KAVpeak, and TLA. Although it is similarly described between modalities, RHK showed distinct kinematic characteristics between taekwondo, karate, and muaythai. Based on these results, coaches and athletes can improve their RHK technique according to the specificities of each combat sport. Specifically, it is suggested that combat strategies should aim to increase the distance from the opponent during combat for muaythai athletes, whereas taekwondo and karate athletes should focus on decreasing it.